Studies of radiation health effects inform EPA actions. (27th September 2019) - Pawel, David; Boyd, Michael
Abstract: In 1970, the US Environmental Protection Agency (EPA) was given the responsibility to provide guidance to other federal agencies in the formulation of radiation protection standards. To carry out its federal guidance responsibilities and protect human health, the EPA must estimate risk at low doses to limit the risk of radiogenic cancers from environmental exposures. These risk estimates are based on models which conform to the linear no threshold (LNT) hypothesis. A cancer risk model conforms to the LNT hypothesis if the excess risk of cancer at low doses increases approximately proportional to dose, with no threshold. Risk models with a linear-quadratic dose response can satisfy the LNT hypothesis. Based on careful review of evidence from epidemiological and radiobiological studies, authoritative scientific bodies have repeatedly endorsed the use of LNT models for estimating and regulating risk and concluded that despite uncertainties at low dose and dose rates, the LNT model remains the most practical and implementable model for radiation protection. This article describes the rationale underlying the use of LNT models for calculating risk for low dose and dose rate exposures and discusses some of the epidemiological evidence which inform on its continued use.